Teaching Performance Evaluation Model: Preparation for Student Learning within the Framework for Teacher Good Performance - Gálvez Suarez, Eric (2018)
The objective of the present research work was to design a teaching performance evaluation model based on the domain Preparation for student learning within the Framework for Teacher Good Performance. The study is based on an applied-projective method, with a qualitative educational approach. The instrument was applied to 94 teachers and 6 managers from 4 public educational institutions. The results show low levels of performance related to the preparation of learning and discontinuity of the purposes in the evaluation process, thus concluding with the development of a teaching evaluation model that integrates a new way of evaluation, from the perspective of teacher reflection and improvement of his performance.